Exploring the barriers to the development of organizational health literacy in health institutions to meet the needs of older patients from multiple perspectives: a mixed-methods study - Jie Zhu; Haiyan Fu; Angela Y. M. Leung; Yining Zhang; Jingwen Lin; Yijing Li; Yanru Kang; Runjie Sun; Xinqi Xu; Ping Hou; Pei Duan; Jiayuan Tu; et al. (BMC Geriatrics)
Abstract Background The latest evidence on health literacy in China revealed that only 8% of individuals aged 65–69 years, a segment of the geriatric population, possess adequate health literacy levels, indicating a low level in China. Studies have demonstrated that improving the organizational health literacy of healthcare institutions is a crucial approach to addressing low health literacy among older patients. Objective To explore the obstacles hindering the advancement of organizational health literacy in healthcare institutions in meeting the needs of older patients. Design A mixed-methods approach was employed to investigate both the status and barriers to the establishment of organizational health literacy within two healthcare institutions. Participants Participants included older individuals aged over 60, clinical staff, and managerial personnel from these two health institutions. Methods This research utilized the social-ecological model as its theoretical foundation and utilized a mixed-methods approach to examine the current status and challenges in developing organizational health literacy within healthcare institutions. Initially, a survey using a questionnaire (n = 178) was conducted among older patients to evaluate the establishment of organizational health literacy from their perspective. Following this, interviews (n = 22) were carried out with administrators, clinical personnel, and elderly patients to identify the barriers hindering the development of organizational health literacy within healthcare institutions. Results Quantitative research indicates that health institutions have been less accommodating to the requirements of older patients, with health information dissemination and communication emerging as the weakest areas. Qualitative investigations revealed three key influencing factors: patient-related factors, including physiological and cognitive decline, as well as low educational attainment among older patients; organizational factors, including inadequate clinical staff numbers, deficient long-term systematic training, and a digital divide resulting from health institutions’ digital advancements; and policy-related factors indicating a lack of regulations governing the establishment of organizational health literacy within healthcare institutions. Conclusion The two most vulnerable aspects of OHL in medical institutions regarding the needs of older patients are health information and communication. The factors influencing the construction of OHL in medical institutions are multifaceted, encompassing micro, meso, and macro levels. At the macro level, it is essential for medical institutions to enhance leadership awareness of OHL and to incorporate its development into institutional strategic plans. At the meso-level, medical institutions should be made to optimize the medical environment for elderly patients and to prioritize health literacy training for medical staff. At the micro level, attention must be given to the characteristics and needs of elderly patients. Ultimately, by implementing a comprehensive construction of intervention strategies, the response ability of medical institutions to the needs of elderly patients can be enhanced.